PENERTIBAN USAHA SALON TANPA IZIN DI KOTA PEKANBARU (STUDI KASUS DI KECAMATAN TAMPAN) - Oktaria, Fika; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru local regulation number 8 in 2012 about Interference Permit Retribution is one of policy made by government of pekanbaru city to organize and regulate the entrepreneurs where their business include into interference business in pekanbaru city. This regulation was made to follow where this regulation aim to the entrepreneurs in running their business accordance with condition and regulation in force and with regulation the existence of these regulation salon owner are required to have permit and pay permit retribution on bisiness they have.The aim of tis research to anaylize local regulation are already running well or not, as well as to find out the factors that influence the implementation of this regulation. This research was conducted in tampan sub of pekanbaru city, by using descriptive quatitative methods with data collection technique through observation and interviews. This research was conducted with the use of surveillance according to subrantas theory.The result of this research show that the implementation of these regulation has not been effective. The goal of existence of this regulation not yet achieve such as creating ublic order and to increase local income areal regional income area (PAD). This policy has been in force for 2 years but have yet to get the desied result. The lack of efficiency of this regulation due to alack of coordination between technical implementing pollius team and government who not strictiy in carrying out these regulation, as well as the in responsifity of the objective target of this policy very low or do not care obout implementation of this pomey.Keyword : curbing, salon business, permit